Mobilizing Stakeholders in Preserving and Revitalizing the Traditional Craft of Balinese Songket Textile of the Women Weavers - Miel S. Bongon; Carlos M. Raymundo; Leovegildo V. Santelices; Romeo O. Sumayo; Demosthenes B. Vibandor; Marcelo Roland C. Villafuerte; Romeo M. Sumayo; Ni Komang Arini Setyawati; I Wayan Rideng; Ni Luh Made Mahendrawati; I Made Mardika; Ni Nengah Seri Ekayani; I Nyoman Muliana; Putu Ayu Sriasih Wesna; Anak Agung Dian Susanti (Lembaga Pengabdian Kepada Masyarakat, Universitas Warmadewa, 2024)
The study sought to identify emerging challenges the Balinese women handweavers encountered through interview documentation and community immersion. Songket textiles, aside from being one of the cultural products of Indonesia, were usually utilized on special occasions like weddings, rituals, and other social engagements, commonly for the upper-class individuals of society. The analyzed documented challenges paved the way for the policy recommendation to protect handweaving engagement in terms of its compensation, appreciation, and empowerment. Handweaving, aside from manifesting Balinese culture, clamored for governmental support and social appreciation, catalyzing its preservation and revitalization as they continued to embody their identity. Formulating a developmental plan facilitates the step-by-step process of ensuring the attainment of the long-term sustainable development goals for the Songket Industry.